Early recovery following lower limb arthroplasty: qualitative interviews with patients undergoing elective hip and knee replacement surgery. Initial phase in the development of a patient-reported outcome measure (PROM) - Strickland, L; Kelly, L; Hamilton, T; Murray, D; Pandit, H; Jenkinson, C (Wiley, 2017)
Aims and objectives: The aim of this study was to explore the patients’ perspective of surgery and early recovery when undergoing lower limb (hip or knee) arthroplasty. Background: Lower limb arthroplasty is a commonly performed procedure for symptomatic arthritis which has not responded to conservative medical treatment. Each patients’ perspective of the surgical process and early recovery period impacts on their quality of life. Design: Open, semi-structured qualitative interviews were utilised to allow for a deeper understanding of the patient perspective when undergoing a hip or knee arthroplasty. Methods: Following ethical approval, thirty patients were interviewed between August and November 2016 during the perioperative period while undergoing an elective hip or knee arthroplasty (n=30). The interviews were performed between the day of surgery and a nine week postoperative clinic appointment. Data were analysed using an in depth narrative thematic analysis method. NVivo qualitative data analysis software was used. Results: Seven main themes evolved from the interviews: ‘improving function and mobility’, ‘pain’, ‘experiences of healthcare’, ‘support from others’, ‘involvement and understanding of care decisions’, ‘behaviour and coping’ and ‘fatigue and sleeping’. Conclusions: The early postoperative recovery period is of vital importance to all surgical patients. This is no different for the orthopaedic patient. However, identifying key self-reported areas of importance from patients can guide clinical focus for healthcare professionals. Relevance to clinical practice: To have specific patient-reported information regarding key areas of importance during the perioperative phase is invaluable when caring for the orthopaedic surgical patient. It gives insight and understanding to this increasing population group. This study has also served as a starting point in the development of a questionnaire which may be used to assess interventions in the lower limb arthroplasty population. These results will influence both items and content of the questionnaire.